Analysis of the application of the galvanic circuits in schemes of the catodic protection for underground papelines - Azyukovsky A. A.; Didevich E. A. (Журнал інженерних наук)
The possibility of using anode earthing in an assembly with a container is considered. Ensuring the integrity of the pipeline is a topical issue in connection with the environmental and economic consequences. The process of pipeline protection is accompanied by the removal of metal particles, at the electronic level. When creating a potential difference, the current will shift from the anode to the cathode. In the process of this shift electrons from the anode earthing switch are moved to the pipeline under the influence of an electromagnetic field. It thereby destroying the anode and expanding the metal elements under protection. Description of galvanic capacitive solution for cathodic protection stations is executed. To exclude the effect of the electrochemical protection on the cathode and, thus, improve the protection of the pipeline.